Orbital myiasis on recurrent undifferentiated carcinoma in the COVID-19 era: a case report and brief review of the literature - Mansooreh Jamshidian-Tehrani (SpringerOpen, 2021)
Abstract Background Myiasis is defined as the infestation of living tissues by Diptera larvae. Ophthalmic involvement occurs in less than 5% of cases. As the most uncommon type of involvement, orbital myiasis usually affects patients with poor personal hygiene, a low socioeconomic status, a history of surgery, and cancer. Findings In January 2020, an 89-year-old man presented to the Oculoplastic Department of Farabi Eye Hospital (Iran) with a history of left-side progressive orbital mass for six months. A large infiltrative mass of the left orbit with extension to the globe, periorbita, and adnexa was remarkable at the presentation, and its appearance suggested malignancy. Our findings persuaded us to perform exenteration and histopathological evaluation which were reported as “undifferentiated carcinoma”. Regular follow-up visits were recommended. In June 2020, with a 3-month delay, the patient presented with the recurrence of the mass complicated with mobile alive larva. Examinations revealed numerous maggots crawling out of an ulcerative and foul-smelling lesion. He stated that fear of COVID-19 infection postponed his follow-up visit. The patient underwent immediate mechanical removal of larvae, followed by wide local excision of the mass. Conclusion Patients with carcinoma of the adnexal tissues seem to be more prone to myiasis infestation even though it is an uncommon disease. Since COVID-19 is an ongoing pandemic with no end in sight appropriate protocols should be implemented to prevent loss of follow-up in these high risk patients.